Turning a Collagenesis-Inducing Peptide Into a Potent Antibacterial and Antibiofilm Agent Against Multidrug-Resistant Gram-Negative Bacteria - Gomes, Ana; Bessa, Lucinda J.; Fernandes, Iva; Ferraz, Ricardo; Mateus, Nuno; Gameiro, Paula; Teixeira, Cátia; Gomes, Paula (Frontiers in Microbiology, 2019)
Antimicrobial resistance is becoming one the most serious health threats worldwide, as it not only hampers effective treatment of infectious diseases using current antibiotics, but also dramatically increases the risks of medical procedures like surgery, transplantation, bone and dental implantation, chemotherapy, or chronic wound management. To date, there are no effective measures to tackle life-threatening nosocomial infections caused by multidrug resistant bacterial species, of which Gram-negative species within the so-called “ESKAPE” pathogens are the most worrisome. Many such bacteria are frequently isolated from severely infected skin lesions such as diabetic foot ulcers. In this connection, we are pursuing new peptide constructs encompassing antimicrobial and collagenesis-inducing motifs, to tackle skin and soft tissue infections by exerting a dual effect: antimicrobial protection and faster healing of the wound. This produced peptide 3.1-PP4 showed MIC values as low as 1.0 M and 2.1 M against Escherichia coli and Pseudomonas aeruginosa, respectively, and low toxicity to HFF-1 human fibroblasts. Remarkably, the peptide was also potent against multidrug-resistant isolates of Klebsiella pneumoniae, E. coli and P. aeruginosa (MIC values between 0.5 and 4.1 M), and hampered the formation of/disaggregated K. pneumoniae biofilms of resistant clinical isolates. Moreover, this notable hybrid peptide retained the collagenesis-inducing behavior of the reference cosmeceutical peptide C16-PP4 (“Matrixyl”). In conclusion, 3.1-PP4 is a highly promising lead towards development of a topical treatment for severely infected skin injuries.